2001
DOI: 10.1038/sj.mp.4000940
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive interference is associated with neuronal marker N-acetyl aspartate in the anterior cingulate cortex: an in vivo 1H-MRS study of the Stroop Color-Word task

Abstract: The neurobiology of cognitive interference is unknown. Previous brain imaging studies using the Stroop Color-Word (SCW) task indicate involvement of the cingulate cortex cognitive division. The present study examines interrelationships between regional brain N-Acetyl aspartate (NAA) levels (as identified by in vivo proton magnetic resonance spectroscopy in the right and left anterior cingulate cortex (ACC), dorsolateral prefrontal cortex, orbitofrontal cortex and thalamus) and cognitive interference (as measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 67 publications
(147 reference statements)
2
18
0
Order By: Relevance
“…Concurrently, we acquired 1 H-MRS data from the dACC to obtain measures of specific brain metabolites that mark distinct aspects of neuronal integrity and function. In light of previous findings, 20 NAA was of particular interest. Combining 1 H-MRS and fMRI measurements allowed us to derive a detailed neurobiological characterization of dACC biochemistry and functional physiology in long-term opiatedependent subjects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrently, we acquired 1 H-MRS data from the dACC to obtain measures of specific brain metabolites that mark distinct aspects of neuronal integrity and function. In light of previous findings, 20 NAA was of particular interest. Combining 1 H-MRS and fMRI measurements allowed us to derive a detailed neurobiological characterization of dACC biochemistry and functional physiology in long-term opiatedependent subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a recent study of healthy individuals by Grachev et al 20 used proton magnetic resonance spectroscopy ( 1 H-MRS; an in vivo approach to measuring brain metabolite concentrations) to demonstrate a direct association between concentrations of a specific neuronal metabolite (N-acetylaspartate (NAA)) in the dACC and individual differences in measures of behavioural control (i.e., reaction timeinterference). NAA is a metabolite produced within neuronal mitochondria that reflects neuronal density and functional viability.…”
Section: Introductionmentioning
confidence: 99%
“…As recent studies have shown that lower values of NAA correlate directly with lower ATP values (Manji, Moore, Rajkowska, & Chen, 2000), NAA can be regarded as a marker of neuronal viability & metabolism (Grachev, Kumar, Ramachandran, & Szeverenyi, 2001; Ohrmann et al, 2004; Tsai & Coyle, 1995). Given that levels of NAA have been found to correlate with measures of selective attention in other studies (Grachev et al, 2001) our data suggest that relative preservation of neurochemical integrity in posterior regions such as the PVC may allow MA abusers to efficiently process spatial information, at least on the task employed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…A noteworthy exception was the term 'cognitive control' itself. Only three of thirty papers selected to contain this term indicated that 'cognitive control' was measured using a specific test, [19][20][21] and Numbers are the number of papers (unique PMID identifiers) found in the PubMed database. Diagonals show size of the paper in PubMed.…”
Section: Methodsmentioning
confidence: 99%